1995
DOI: 10.1254/jjp.68.71
|View full text |Cite
|
Sign up to set email alerts
|

Neither the 5-HT1A- nor the 5-HT2-Receptor Subtype Mediates the Effect of Fluvoxamine, a Selective Serotonin Reuptake Inhibitor, on Forced-Swimming-Induced Immobility in Mice

Abstract: ABSTRACT-The effect of fluvoxamine, a selective serotonin (5-HT) reuptake inhibitor, was studied in the forced-swimming test, a model of depression, in mice. Fluvoxamine at 60 mg/kg, p.o. significantly decreased the immobility time in the forced-swimming test. A similar effect was observed by the selective norepinephrine reuptake inhibitor desipramine at the same dose. Furthermore, the suppression of immobility time was slightly potentiated by repeated administration of fluvoxamine, and a significant effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…SB242084 restored citalopram’s effect in the forced swimming test in DBA/2 mice, possibly because this antagonist enhances the effect on extracellular 5‐HT (Calcagno et al. 2009) whereas pharmacological blockade or genetic deletion of 5‐HT 2C receptors had no clear effects in mice and rats already responding to SSRIs (Egawa et al. 1995; Cryan and Lucki 2000; Yamada and Sugimoto 2002).…”
Section: Discussionmentioning
confidence: 99%
“…SB242084 restored citalopram’s effect in the forced swimming test in DBA/2 mice, possibly because this antagonist enhances the effect on extracellular 5‐HT (Calcagno et al. 2009) whereas pharmacological blockade or genetic deletion of 5‐HT 2C receptors had no clear effects in mice and rats already responding to SSRIs (Egawa et al. 1995; Cryan and Lucki 2000; Yamada and Sugimoto 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have already found that fluvoxamine has suppressive effects on immobility in the depression models of mice, tail-suspension (5) and forced-swimming (6). However, there is as yet no established screening model for OCD.…”
mentioning
confidence: 99%
“…injections of saline solution (0.9% NaCl). The antidepressant dose of fluoxetine (10 mg/kg day) was chosen according to previous studies that demonstrated a robust effect in the forced swimming test (FST) employing similar conditions . The fluoxetine dose lacking antidepressant effect (1 mg/kg day) was also chosen according to previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…The antidepressant dose of fluoxetine (10 mg/kg day) was chosen according to previous studies that demonstrated a robust effect in the forced swimming test (FST) employing similar conditions. 17,24,25 The fluoxetine dose lacking antidepressant effect (1 mg/kg day) was also chosen according to previous studies. 17,26 Rats were in- a Values are expressed as g/100 g total fatty acids, determined by gas chromatography according to previous studies.…”
Section: Experimental Designmentioning
confidence: 99%